PENGARUH KETIDAKPUASAN DAN IKLAN PRODUK PESAING TERHADAP PERILAKU BRAND SWITCHING DENGAN KEBUTUHAN MENCARI VARIASI SEBAGAI VARIABEL MODERATINGNYA ( Studi pada mantan pengguna kartu Pra Bayar IM3 di lingkungan mahasiswa FISIP Universitas Diponegoro ) - Janatien Rosi; Naili Farida; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2012)
This study aims to determine the effect of dissatisfaction and advertisement of competing products towards brand switching behaviour of IM3 consumers through variety seeking as a moderating variable. The sampling technique used was purposive sampling. Whereas, the method of analysis used in this research was path analysis. The result of calculation indicated that each of the variable of dissatisfaction, variable of competing product advertisements, and variable of variety seeking has a positive, significant effect on variable of brand-switching behaviour. The effect caused by the variable of dissatisfaction towards variable of brand-switching behaviour is the biggest, it is as much as 57.5%. Simultaneously has a positive, significant effect towards variable of brand-switching behaviour as much as 65.5%, while the remaining is 34.5% is explained by the other factors. Based on the path analysis calculation, it was proved that variable of variety seeking as a moderating variable can be a strengthening relationship mediator between variable of competing product advertisement and variable of brand switching behavior. Meanwhile, the variety seeking variable exactly being a mediator which weaken the relevance of dissatisfaction variable to the brand switching behavior. The recommendations of this research are the company should improve the quality of service, expand the signal coverage, upgrade the signal strength, make the sound of product clearer. The company also should increase the frequency of publicity in several media. The creativity of advertising strategy also should be increase in term of showing/ appearance, design, and the message that will be delivered. Its advertisement should explain the brand excellence comparing with the competitors to prevent the customers who like variations.